2016
DOI: 10.1002/dmrr.2828
|View full text |Cite
|
Sign up to set email alerts
|

Benefits of a Paleolithic diet with and without supervised exercise on fat mass, insulin sensitivity, and glycemic control: a randomized controlled trial in individuals with type 2 diabetes

Abstract: Background Means to reduce future risk for cardiovascular disease in subjects with type 2 diabetes are urgently needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
114
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 122 publications
(122 citation statements)
references
References 49 publications
4
114
0
1
Order By: Relevance
“…The main results of the intervention have been previously published [25]. In the present substudy, we found no betweengroup differences in baseline characteristics except a higher fasting glucose in the PD-EX group (Table 1).…”
Section: Participant Characteristics and Intervention Validationsupporting
confidence: 71%
See 1 more Smart Citation
“…The main results of the intervention have been previously published [25]. In the present substudy, we found no betweengroup differences in baseline characteristics except a higher fasting glucose in the PD-EX group (Table 1).…”
Section: Participant Characteristics and Intervention Validationsupporting
confidence: 71%
“…In addition, the participants were randomised to receive either supervised exercise training for 3 h per week (PD-EX group) or standard care exercise recommendations (PD group). The reduction of fat mass was the primary endpoint of this study and has been published previously [25]. The outcome measurements of this article are secondary endpoints (liver fat and peripheral and hepatic insulin sensitivity) and secondary analyses (IMCL).…”
Section: Methodsmentioning
confidence: 99%
“…The PD causes a greater weight loss than a conventional diet according to Nordic Nutrition Recommendations among obese women without type 2 diabetes (21). Furthermore, the PD has been shown to improve insulin sensitivity and reduce hepatic lipid levels among patients with type 2 diabetes (22,23). In general, the PD excludes the intake of dairy products, salt, refined sugar and grains, while the intake of vegetables, lean meat, fish and nuts is increased (21,22).…”
Section: Introductionmentioning
confidence: 99%
“…Mediterranean diet is one example that is in agreement with these requirements . In addition to that, Palaeolithic diet, which was shown to improve fat mass, insulin sensitivity, and HbA1c in patients with T2DM, adds more restriction to legumes, dairy products, and grains . Carbohydrate restriction is one of the dietary approach that does not in line with the American Diabetes Association's recommendation.…”
Section: Introductionmentioning
confidence: 99%